Oxidation Behavior of Quaternary Co-20Re-25Cr-3Si Alloy at Laboratory Air - Liu, Mingfeng; Xiang, Junhuai; Wei, Hua; Pan, Xiuhong; Xu, Xunhu; Wang, Ling; Zhang, Shuai (Frontiers in Materials, 2021)
The iso-thermal oxidation of the quaternary Co-20Re-25Cr-3Si alloy at 1000-1200 ℃ under laboratory air for 24 h has been studied. The kinetics at 1000-1200 ℃ conform quite well to parabolic law during the whole oxidation process with the value of oxidation activation energy equal to 220.74 kJ/mol. Unlike the case of the experimental condition of 0.1 MPa pure oxygen, a dense and continuous layer of Cr2O3 in contact with the alloy has formed on Co-20Re-25Cr-3Si alloy at 1000-1200 ℃ under laboratory air, accounting for the good oxidation resistance of the alloy. A 79% drop in oxygen pressure has changed the oxidation mode from catastrophic oxidation to mild oxidation. The thickness of the protective Cr2O3 layer decreases when temperature increases. Therefore, Co-20Re-25Cr-3Si alloy shows the best oxidation resistance at 1000 ℃. Moreover, from another perspective, compared with Co-17Re-23Cr-3Si alloy, the addition of about 2% Cr can also improve the oxidation resistance of the alloy greatly by forming the protective Cr2O3 layer.